Clinical Viability for Immediate Loading of Dental Implants: Part II-Treatment Alternatives - Goiato, Marcelo Coelho [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Ricardo Barao, Valentim Adelino [UNESP]; Santos, Daniela Micheline dos [UNESP]; de Carvalho, Bruno Machado [UNESP]; Magro Filho, Osvaldo [UNESP]; Garcia, Idelmo Rangel [UNESP] (Lippincott Williams & Wilkins, 2009)
The treatment with implants aims to obtain a direct interface between bone and implant. The implant is kept load-free during 4 to 6 months in the 2-stage procedure, which is considered a requisite for osseointegration. However, this period is based on empirical principles and uncomfortable for patient. So, the immediate loading protocol was Suggested to submit implants to occlusal function after placement. This protocol has been applied for several conditions of edentulism. The aim of this study was to evaluate the treatment alternatives for immediate loading of complete and partial edentulous patients. In general, the studies have demonstrated high previsibility for rehabilitation of complete edentulous arches with full-arch, implant-supported prosthesis. The rehabilitation with immediate loading for maxillary overdenture is questionable because there is no longitudinal study in literature. The studies with partial edentulous arches have demonstrated high success rates for implants placed in the mandibular and maxillary anterior region. Additional care is recommended for posterior region mainly in the maxillary arch, and further studies are suggested to corroborate this treatment.
Keywords: Immediate loading; implants dental